CAUSES AND PREVENTION STRATEGIES OF DENTAL CARIES AMONG ADOLESCENTS - A’zamqulova Durdona Bahriddin qizi (Western European Studies, 2025)
This article analyzes effective strategies and preventive measures to combat the widespread occurrence of dental caries among adolescents. Dental caries is one of the most common and serious oral health problems among young people, including my peers [1]. The main causes include unhealthy diet, poor oral hygiene habits, socioeconomic factors, and genetic predisposition [2][4]. These causes are highlighted in recent journals and scientific sources. The paper discusses the importance of health education, improvement of oral hygiene, rational nutrition, and preventive dentistry [6]. In addition, the role of individualized approaches and genetic factors in prevention is emphasized [4]. The study provides recommendations and conclusions based on up-to-date scientific literature and the guidelines of international health organizations [1][3][7]. The article may be useful for dental students, practitioners, parents, and adolescents themselves
Keywords: Caries; Adolescents; Prophylaxis